Training monitoring and effect of training variables on wellness score in elite male fencers - Yildirim, E.; Cinemre, S. A.; Zengin, H. Y. (Turkish Journal of Sport and Exercise, 2023)
Subjective measures such as well-being indices may be beneficial to balance fatigue and recovery on the fatigue continuum and awareness of well-being is considered a useful sign for identifying NFOR status. Recovery and neuromuscular fatigue process from training may be delayed because of the eccentric component during a stretch-shortening cycle (SSC) type activities and needs to be well monitored during fencing training and matches. The aim of the study is to investigate training monitoring of elite male fencing athletes aged 15-23 and to examine the variables that affect wellness during intensified training periods. The study includes 16 elite men's saber fencers who train regularly and comprised of 139 data concentrated on training and 6 data engrossed on competitions. These data were examined throughout 2 different time periods and an overall duration. Wellness scores, acute/chronic workload ratio (ACWR) and monotony scores were collected. The main findings of this study, in training loads (AU) a statistically significant difference weren`t observed between periods, but in wellness scores, a significant difference was observed between periods (acute load, p=0.861; hooper index, p=0.003). ACWR (p=0,6103) and monotony (p=0,4810) scores were not observed to be significant predictors of wellness both univariate and multivariate. In summation, This investigation concluded and reinforced the notion that the wellness score is a vital criterion in training and performance monitoring. It was discovered and noted that the continuity of the trainings and the increased intensity of the competition resulted in the wellness score to increase during the second period.